Image forming system and image forming method

The image formation system addresses charge leakage and image concentration issues in low-temperature and low-humidity environments by using a two-component developer with controlled silicon content and a (meta)acrylate-coated resin, ensuring stable image quality.

JP2025015868APending Publication Date: 2025-01-31KONICA MINOLTA INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023118728
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

Image formation systems using aluminum alloys with high silicon content experience charge leakage and reduced image concentration in low-temperature and low-humidity environments, leading to local image defects such as white spots.

Method used

An image formation system utilizing a two-component developer with a carrier having a specific static resistance value and a coated resin, where the aluminum alloy used has controlled silicon content and surface roughness, along with a coating resin derived from (meta)acrylate, to prevent charge leakage and maintain image concentration.

Benefits of technology

The system effectively suppresses charge leakage and maintains image concentration in low-temperature and low-humidity conditions, preventing local image defects by moderating charge release from carrier particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015868000001_ABST
    Figure 2025015868000001_ABST
Patent Text Reader

Abstract

To provide an image forming system and an image forming method that can prevent a local image defect due to leakage of electric charges and a reduction in image density in a low temperature and low humidity environment.SOLUTION: An image forming system uses two-component developer, and an image forming apparatus comprising at least either one of a photoreceptor using a support made of an aluminum alloy or a developer carrier made of an aluminum alloy. The static resistance value of a carrier included in the two-component developer is within a range of 1.0×1012 to 5.0×1014 Ω cm. The content of silicon in the aluminum alloy forming at least the support of the photoreceptor or the developer carrier is within a range of more than 0.6 mass% and at most 12.6 mass%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an image forming system and an image forming method, and more particularly to an image forming system capable of suppressing localized image defects caused by charge leakage and reduction in image density in a low-temperature, low-humidity environment. [Background technology]

[0002] In recent years, there has been a demand for reducing the environmental impact of various members constituting the main body of an electrophotographic image forming apparatus.

[0003] One possible way to reduce the environmental burden is to use materials that emit less carbon dioxide per unit mass when manufacturing the various components mentioned above. For example, in the case of components that use aluminum alloys, the process of manufacturing aluminum from bauxite emits a large amount of carbon dioxide, which places a large burden on the environment. In contrast, by using aluminum alloys recycled from aluminum-containing waste materials, the process of manufacturing aluminum from bauxite can be eliminated. This can significantly reduce carbon dioxide emissions and lessen the environmental burden.

[0004] Metal elements other than aluminum are added to these aluminum alloys to control their physical properties and workability, regardless of whether they are recycled or not. In particular, silicon is added to various types of aluminum alloys because it affects heat resistance, thermal expansion, and workability.

[0005] As an example of using such silicon-containing aluminum alloys in components of electrophotographic image forming devices, for example, Patent Document 1 discloses an electrophotographic photoreceptor using a silicon-containing aluminum alloy for the support.

[0006] Moreover, Patent Document 2 discloses a developer carrier using an aluminum alloy containing silicon.

[0007] Incidentally, when producing aluminum alloys by recycling as described above, it is necessary to detect and remove impurities including silicon and adjust their contents.

[0008] However, because silicon is difficult to separate and remove, aluminum alloys produced through recycling contain more silicon than necessary, which means that when used in the above-mentioned components, they may not achieve the desired performance.

[0009] Therefore, there has been a demand for improvements that would enable desired performance to be achieved even when using a photoconductor and a developer carrier made of an aluminum alloy having a high silicon content as described above. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2022-132142 A [Patent Document 2] JP 2008-102502 A Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention has been made in consideration of the above problems and circumstances, and its problem to be solved is to provide an image forming system and an image forming method that can suppress localized image defects caused by charge leakage and reduction in image density in low-temperature, low-humidity environments. [Means for solving the problem]

[0012] In order to solve the above problems, the present inventors have investigated the causes of the above problems and have found that the above problems can be solved by combining a photoconductor support or developer carrier having an aluminum alloy with a silicon content within a specific range and a two-component developer having a carrier static resistance value within a specific range, thereby arriving at the present invention. That is, the above-mentioned problems of the present invention are solved by the following means.

[0013] 1. An image forming system using a two-component developer and an image forming apparatus equipped with at least one of a photoconductor using an aluminum alloy support or a developer carrier made of an aluminum alloy, The static resistance value of the carrier contained in the two-component developer is 1.0×10 12 ~5.0×10 14 In the range of Ω cm, and The silicon content in the aluminum alloy forming at least the support of the photoreceptor or the developer carrier is in the range of more than 0.6 mass % and not more than 12.6 mass %. 1. An image forming system comprising:

[0014] 2. The carrier is made of carrier particles in which at least the surface of a core particle is coated with a coating resin, The coating resin has a structure derived from (meth)acrylate. 2. The image forming system according to claim 1,

[0015] 3. The coating resin contains at least one of carbon black, magnesium oxide, and titanium dioxide. 3. The image forming system according to claim 2,

[0016] 4. The exposed area ratio of the core particles on the surface of the carrier particle is within a range of 1.0% or more and less than 10.0% of the surface area of ​​the core particles. 3. The image forming system according to claim 2,

[0017] 5. The silicon content is in the range of more than 0.8% by mass and not more than 12.6% by mass with respect to the total amount of the aluminum alloy forming at least the support body of the photoreceptor or the developer carrier. 2. The image forming system according to claim 1,

[0018] 6. The coating resin has a structure derived from an alicyclic (meth)acrylate. 3. The image forming system according to claim 2,

[0019] 7. The static resistance of the carrier is 1.0 x 10 12.5 ~1.5×10 14 Within the range of Ω·cm 2. The image forming system according to claim 1,

[0020] 8. The absolute value of the development potential difference is within the range of 300 to 800 V. 2. The image forming system according to claim 1,

[0021] 9. An image forming method using a two-component developer and an image forming apparatus equipped with at least one of a photoreceptor using an aluminum alloy support or a developer carrier made of an aluminum alloy, The static resistance value of the carrier contained in the two-component developer is 1.0×10 12 ~5.0×10 14 In the range of Ω cm, and The silicon content in the aluminum alloy forming at least the support of the photoreceptor or the developer carrier is in the range of more than 0.6 mass % and not more than 12.6 mass %. 1. An image forming method comprising: Effect of the Invention

[0022] It is possible to provide an image forming system and an image forming method that can suppress localized image defects caused by charge leakage and reduction in image density in a low-temperature, low-humidity environment.

[0023] Although the mechanism by which the effects of the present invention are expressed or the mechanism of action has not been clarified, it is speculated as follows.

[0024] The image forming system of the present invention is an image forming apparatus using a two-component developer and at least one of a photoreceptor using an aluminum alloy support or a developer carrier made of an aluminum alloy, wherein the static resistance value of the carrier contained in the two-component developer is 1.0×10 12 ~5.0×10 14 The electrical resistance of the photoconductor is in the range of Ω·cm, and the silicon content in the aluminum alloy forming at least the support body of the photoreceptor or the developer carrier is in the range of more than 0.6 mass % and not more than 12.6 mass %.

[0025] The surface of the support of the photoreceptor or the developer carrier made of an aluminum alloy becomes non-uniform in composition and shape as the silicon content in the aluminum alloy increases, and the surface shape of the support also becomes non-uniform, with many coarse crystals (protrusions) due to the eutectic of silicon and aluminum appearing on the surface.

[0026] In order to impart an appropriate surface roughness to the surface of the support member of the photoreceptor or the surface of the developer carrier made of an aluminum alloy, it is conceivable to subject the surface to a surface treatment such as cutting or blasting.

[0027] However, when the above-mentioned surface treatment is performed, the above-mentioned coarse crystal (convex portion) portions may be locally detached or remain on the cut surface during the treatment, which may result in the formation of unintended fine irregularities.

[0028] As a result, the application of voltage during development can easily cause charge leakage between the convex parts on the surface of the developer carrier and the convex parts on the surface of the photosensitive member support, resulting in localized image defects (white spots) due to a partial drop in potential.

[0029] In the present invention, during image formation, any one of three combinations is used: (1) a photoconductor support made of an aluminum alloy having a silicon content within a specific range and a two-component developer, (2) a developer carrier made of an aluminum alloy having a silicon content within a specific range and a two-component developer, or (3) a photoconductor support made of an aluminum alloy having a silicon content within a specific range and a developer carrier made of an aluminum alloy having a silicon content within a specific range and a two-component developer. Furthermore, the resistance value of the carrier contained in the two-component developer is adjusted to within a specific range.

[0030] It is believed that this allows an appropriate amount of charge to be released from the carrier particles when the toner and carrier are frictionally charged, suppressing excessive charging of the toner and preventing localized image defects (white spots). [Brief description of the drawings]

[0031] [Figure 1] An external view of a developer carrier having a developing sleeve [Diagram 2] Cross-sectional view of a developer carrier in which the shaft does not pass through the magnet roller [Diagram 3] Cross-sectional view of a developer carrier in which the shaft passes through a magnet roller [Figure 4] FIG. 1 is a cross-sectional view illustrating an example of a configuration of an image forming apparatus according to the present invention. [Diagram 5] An example diagram showing the Vpp value of AC voltage DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The image forming system of the present invention is an image forming apparatus using a two-component developer and at least one of a photoreceptor using an aluminum alloy support or a developer carrier made of an aluminum alloy, wherein the static resistance value of the carrier contained in the two-component developer is 1.0×10 12 ~5.0×10 14The electrical resistance of the photoconductor is in the range of Ω·cm, and the silicon content in the aluminum alloy forming at least the support body of the photoreceptor or the developer carrier is in the range of more than 0.6 mass % and not more than 12.6 mass %. This feature is a technical feature common to or corresponding to each of the following embodiments (aspects).

[0033] As an embodiment of the present invention, it is preferable from the viewpoint of reducing environmental differences in charging that the carrier comprises carrier particles in which at least the surface of a core particle is coated with a coating resin, and the coating resin has a structure derived from (meth)acrylate.

[0034] It is preferable that the coating resin contains at least one of carbon black, magnesium oxide and titanium dioxide, from the viewpoint of adjusting the static resistance value of the carrier.

[0035] It is preferable that the exposed area ratio of the core particle on the carrier particle surface be in the range of 1.0% or more and less than 10.0% of the surface area of ​​the core particle, from the viewpoint of suppressing excessive charging of the carrier particles and suppressing deterioration of the carrier particles.

[0036] From the viewpoint of processability and maintaining surface roughness, it is preferable that the silicon content is in the range of more than 0.8 mass % and not more than 12.6 mass % based on the total amount of the aluminum alloy forming at least the support body of the photoreceptor or the developer carrier.

[0037] It is preferable that the coating resin has a structure derived from a highly hydrophobic alicyclic (meth)acrylate from the viewpoint of further reducing the environmental difference in electrostatic chargeability.

[0038] The static resistance of the carrier is 1.0×10 12.5 ~1.5×10 14 A resistance within the range of Ω·cm is preferable from the viewpoint of suppressing the occurrence of charge leakage.

[0039] It is preferable that the absolute value of the development potential difference is within a range of 300 to 800 V from the viewpoints of suppressing the occurrence of charge leakage and ensuring image density.

[0040] The image forming method of the present invention is an image forming method using a two-component developer and an image forming apparatus equipped with at least one of a photoreceptor using an aluminum alloy support or a developer carrier made of an aluminum alloy, wherein the static resistance value of the carrier contained in the two-component developer is 1.0×10 12 ~5.0×10 14 The aluminum alloy forming at least the support body of the photoreceptor or the developer carrier has a silicon content of more than 0.6 mass % and not more than 12.6 mass %, and can be suitably used in the image forming system of the present invention.

[0041] The present invention, its components, and embodiments for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values ​​before and after the symbol "to" are included as the lower and upper limits.

[0042] [Image forming system] 1. Two-component developer The two-component developer according to the present invention contains a toner and a carrier, and the static resistance value of the carrier is 1.0×10 12 ~5.0×10 14 It is in the range of Ω·cm.

[0043] The two-component developer according to the present invention preferably uses a carrier and a toner, which will be described in detail below. The mixed amount of the toner particles is preferably within a range of 1 to 10% by mass with respect to the entire two-component developer.

[0044] (1.1) Career One of the main roles of the carrier contained in the two-component developer according to the present invention is to be stirred and mixed with the toner in the developing box and to give the toner a desired charge. Another role of the carrier is to act as an electrode between the developing machine and the photoconductor, and to carry the charged toner to the electrostatic latent image on the photoconductor and to function as a carrier material (i.e., a carrier) to form a toner image.

[0045] The carrier is held on the magnet roller by magnetic force, and after acting on the development, it returns to the development box, where it is stirred and mixed again with new toner, and is used repeatedly for a certain period of time. Therefore, in order to stably maintain the desired image characteristics (image density, fog, white spots, gradation, resolution, etc.), it is naturally required that the characteristics of the carrier are stable throughout the period of use.

[0046] The carrier particles constituting the carrier according to the present invention are preferably core particles, which are metal powders such as iron, ferrite, magnetite, etc., coated with a coating resin, as described below. The carrier particles may contain internal additives such as a resistance adjuster, if necessary.

[0047] (1.1.1) Static resistance The static resistance of the carrier according to the present invention is 1.0×10 12 ~5.0×10 14 The static resistance of the carrier is within the range of 1.0×10 12 If the static resistance of the carrier is less than 5.0×10 Ωcm, charge leakage occurs, causing a partial drop in potential and resulting in image defects (white spots). 14 If it exceeds Ωcm, the effective development potential difference becomes small, resulting in a decrease in image density.

[0048] From the above, the static resistance value range of the carrier is 1.0×10 12 ~5.0×10 14 It is more preferable that the resistance is Ω·cm.

[0049] (How to calculate static resistance) The static resistance value of the carrier contained in the two-component developer according to the present invention is calculated as follows: The above "static resistance value" is also called "volume resistivity value".

[0050] First, prepare a two-component developer containing a carrier for which the static resistance value is to be calculated. Then, put the two-component developer into an aqueous solution containing a surfactant, and separate the toner and carrier using ultrasonic waves. After that, use a magnet to extract and separate only the carrier from the two-component developer, and use 1.0 g of the carrier as a sample. Cut the sample into a 1 cm2 cross-sectional area. 2 The insulating cylindrical container is filled with two insulating cylindrical containers, each with a cross-sectional area of ​​1.0 cm2 at the top and bottom. 2 The electrodes are arranged in a .

[0051] Next, the thickness t of the layer formed by the sample is measured under a load of 500g. After that, a DC voltage of 100V is applied with an insulation resistance meter, and the insulation resistance value R [Ω] at that time is read. The thickness t of the layer formed by the sample and the insulation resistance value R are then substituted into the following formula to calculate the static resistance value.

[0052] (Formula 1) Static resistance value [Ω cm] = R (S / t) (In the above formula, R is the insulation resistance value [Ω], S is the cross-sectional area of ​​the layer formed by the sample [cm 2 ], t is the thickness of the layer formed by the sample [cm])

[0053] (1.1.2) Core particles (kinds) The core particles according to the present invention are composed of, for example, metal powder such as iron powder, various ferrites, etc. Among these, ferrites are preferred from the viewpoint of low residual magnetization and favorable magnetic properties.

[0054] The ferrite preferably contains heavy metals such as copper, zinc, nickel, and manganese, and light metals such as alkali metals and alkaline earth metals. Ferrite is a compound represented by the following general formula (1), and the Fe that constitutes the ferrite is 2 O 3The molar ratio y is preferably set to 30 to 95 mol %.

[0055] General formula (1) (MO) x (Fe 2 O 3 ) y (In the above formula, M represents a metal element, and x and y represent molar ratios.)

[0056] When the molar ratio y is within the range of 30 to 95 mol %, a desired magnetization is easily obtained, and there is an advantage that the carrier particles are less likely to adhere to each other when the carrier particles are produced.

[0057] Examples of M in the general formula (1) include manganese (Mn), magnesium (Mg), strontium (Sr), calcium (Ca), titanium (Ti), copper (Cu), zinc (Zn), nickel (Ni), aluminum (Al), silicon (Si), zirconium (Zr), bismuth (Bi), cobalt (Co), lithium (Li), etc. These metal elements may be used alone or in combination of two or more.

[0058] From the viewpoint of obtaining low residual magnetization and suitable magnetic properties, manganese, magnesium, strontium, lithium, copper and zinc are preferred, and among them, manganese and magnesium are more preferred. That is, the core particles according to the present invention are preferably ferrite particles containing at least one of manganese and magnesium. These core particles may be commercially available products or synthetic products.

[0059] (particle size) The particle size of the core particles is the volume-based median diameter (D 50 ) is preferably in the range of 13 to 40 μm, and more preferably in the range of 15 to 30 μm. 50 If the volume-based median diameter (D 50When the average particle diameter is 15 μm or more, adhesion between carrier particles can be prevented, and excellent image quality with little fogging can be provided.

[0060] The volume-based median diameter of the core particles (D 50 ) can be measured, for example, using a laser diffraction particle size distribution measuring device "HELOS" (manufactured by Sympatique) equipped with a wet disperser, and the saturation magnetization of the core material particles can be measured, for example, using a "DC Magnetization Characteristic Automatic Recorder 3257-35" (manufactured by Yokogawa Electric Corporation).

[0061] (Magnetization) The core particles according to the present invention have a saturation magnetization of 30 to 80 Am 2 / kg, and the residual magnetization is preferably within 5.0 Am 2 By using core particles having such magnetic properties, partial aggregation of the carrier particles is prevented, and the two-component developer is more uniformly dispersed on the surface of the developer transport member, making it possible to form a uniform, finely textured toner image without uneven density.

[0062] (Synthesis method) The core particles according to the present invention can be synthesized, for example, by the following method.

[0063] First, the raw materials are appropriately weighed and then pulverized and mixed using a wet media mill, ball mill, or vibration mill. The time required for pulverization and mixing is preferably 0.5 hours or more, more preferably within the range of 1 to 20 hours. The pulverized material thus obtained is pelletized using a pressure molding machine or the like, and then calcined.

[0064] The temperature required for the calcination is preferably within the range of 700 to 1200° C., and the time required for the calcination is preferably within the range of 0.5 to 5 hours. The obtained pulverized material may be pulverized without using a pressure molding machine, or water may be added to the pulverized material after the pulverization to form a slurry, which may be granulated using a spray dryer and then calcined.

[0065] After the calcination, the mixture is further pulverized using a ball mill or a vibration mill, etc. At this time, water may be added and the mixture is pulverized using a wet ball mill or a wet vibration mill, etc. Thereafter, water and a binder such as polyvinyl alcohol (PVA) are added, and a dispersant is added as necessary to adjust the viscosity, followed by granulation and main calcination.

[0066] The temperature of the main firing is preferably within the range of 1000 to 1500°C, and the time of the main firing is preferably within the range of 1 to 24 hours. The above-mentioned pulverizers such as ball mills and vibration mills are not particularly limited, but in order to effectively and uniformly disperse the raw materials, it is preferable to use fine beads having a particle size of 1 cm or less as the media used. In addition, the degree of pulverization can be controlled by adjusting the diameter, composition, and pulverization time of the beads used. The sintered product obtained in this manner is pulverized and classified.

[0067] As a classification method, the particle size is adjusted to a desired particle size using existing methods such as air classification, mesh filtration, and sedimentation. Thereafter, if necessary, the surface of the pulverized and classified fired product is heated at a low temperature to perform an oxide coating treatment, and electrical resistance adjustment can be performed. Furthermore, if necessary, reduction may be performed before the oxide coating treatment, and low magnetic products may be separated by magnetic separation after classification.

[0068] (1.1.3) Coating resin The surface of the core particle according to the present invention is preferably coated with a coating resin, and the coating resin preferably has a structure derived from (meth)acrylate. In this specification, (meth)acrylic means acrylic or methacrylic.

[0069] Examples of the compound having a structure derived from (meth)acrylate include methacrylic acid ester compounds, acrylic acid ester compounds, and alicyclic (meth)acrylic acid ester compounds. In particular, alicyclic (meth)acrylic acid ester compounds are more preferred because they are highly hydrophobic and reduce the amount of water adsorbed by the carrier particles in a high-temperature and high-humidity environment, thereby suppressing a decrease in the amount of charge.

[0070] Examples of methacrylic acid ester compounds include methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, lauryl methacrylate, phenyl methacrylate, benzyl methacrylate, isobornyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminoethyl methacrylate.

[0071] Examples of acrylate compounds include methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, isobutyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, lauryl acrylate, phenyl acrylate, and benzyl acrylate.

[0072] Examples of alicyclic (meth)acrylic acid ester compounds include isobornyl acrylate, dicyclopentanyl acrylate, cyclohexyl acrylate, methylcyclohexyl acrylate, trimethylcyclohexyl acrylate, t-butylcyclohexyl acrylate, cyclohexylphenyl acrylate, cyclododecyl acrylate, adamantyl acrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cycloheptyl methacrylate, cyclooctyl methacrylate, etc. Among these, from the viewpoint of environmental stability of the charge amount, etc., those having a cycloalkyl group having 5 to 8 carbon atoms are preferred, and cyclohexyl methacrylate is more preferred.

[0073] As the monomer constituting the coating resin, a monomer other than the (meth)acrylic acid ester compound may be used.

[0074] Examples of the other monomers include, for example, styrene compounds, methacrylate compounds, acrylate compounds, olefin compounds, vinyl halide compounds, vinyl ester compounds, vinyl ether compounds, vinyl ketone compounds, N-vinyl compounds, vinyl compounds, and acrylic acid or methacrylic acid derivatives.

[0075] Examples of the styrene compound include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-chlorostyrene, 3,4-dichlorostyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, and pn-dodecylstyrene.

[0076] Examples of the (meth)acrylic acid compound include (meth)acrylic acids such as methacrylic acid, acrylic acid, and itaconic acid.

[0077] Examples of the olefin compound include ethylene, propylene, and isobutylene.

[0078] Examples of the vinyl halide compound include vinyl chloride, vinylidene chloride, vinyl bromide, vinyl fluoride, and vinylidene fluoride.

[0079] Examples of the vinyl ester compound include vinyl propionate, vinyl acetate, and vinyl benzoate.

[0080] Examples of the vinyl ether compound include vinyl methyl ether and vinyl ethyl ether.

[0081] Examples of the vinyl ketone compound include vinyl methyl ketone, vinyl ethyl ketone, and vinyl hexyl ketone.

[0082] Examples of the N-vinyl compound include N-vinylcarbazole, N-vinylindole, and N-vinylpyrrolidone.

[0083] Examples of the vinyl compound include vinylnaphthalene and vinylpyridine.

[0084] Examples of the acrylic acid or methacrylic acid derivatives include acrylonitrile, methacrylonitrile, and acrylamide.

[0085] These other monomers may be used alone or in combination of two or more. Among these other monomers, styrene and methyl methacrylate are preferred from the viewpoint of the environmental stability of the charge amount.

[0086] The ratio of the structural units derived from the (meth)acrylic acid ester compound to the structural units derived from other monomers in the coating resin is preferably 10:90 to 100:0, and more preferably 30:70 to 70:30.

[0087] (Weight average molecular weight) The weight average molecular weight of the coating resin, i.e., the polymer obtained by polymerizing the above monomer, is not particularly limited as long as it is within a range in which the effects of the present invention can be effectively exhibited. The weight average molecular weight is preferably within a range of 200,000 to 800,000, more preferably within a range of 300,000 to 700,000. If the weight average molecular weight is 200,000 or more, the resin coating layer formed on the surface of the core particle is not excessively accelerated in attenuation, and is excellent in that it is difficult to cause adhesion of the carrier particle. If the weight average molecular weight is 800,000 or less, a decrease in the charge amount due to the migration of the external additive from the toner particle to the surface of the carrier particle is not caused, and a good charge amount can be maintained for a long period of time.

[0088] The weight average molecular weight is measured by gel permeation chromatography (GPC), and more specifically, the following method may be mentioned.

[0089] The apparatus used was "HLC-8220GPC" (manufactured by Tosoh Corporation) and the column was "TSKguardcolumn SuperHZ-L + TSKgel SuperHZM-M triple series" (manufactured by Tosoh Corporation).

[0090] The column temperature is maintained at 40° C., and tetrahydrofuran (THF) is run as a carrier solvent at a flow rate of 0.35 mL / min.

[0091] The measurement sample is dissolved in tetrahydrofuran at room temperature to a concentration of 1 mg / mL under dissolution conditions of treatment for 10 minutes with a roller stirrer.

[0092] The sample solution is then filtered through a membrane filter with a pore size of 0.2 μm to obtain a sample solution. 10 μL of this sample solution is injected into the device together with the carrier solvent, and detected using a refractive index detector (RI detector).

[0093] The weight-average molecular weight distribution of the measurement sample is calculated using a calibration curve measured using monodisperse polystyrene standard particles. Ten polystyrene samples are used for the calibration curve measurement.

[0094] (Thickness of resin coating layer) The thickness of the resin coating layer is preferably within a range of 0.05 to 4 μm, and more preferably within a range of 0.2 to 3 μm. If the thickness of the resin coating layer is within this range, the chargeability and durability of the carrier particles can be improved.

[0095] The thickness of the resin coating layer can be determined by the following method.

[0096] Using a focused ion beam device "SMI2050" (manufactured by Hitachi High-Tech Science Corporation), the carrier particles are cut along a plane passing through the center of the carrier particles to prepare a measurement sample. The cross section of the measurement sample is observed at a magnification of 5000 times using a transmission electron microscope "JEM-2010F" (manufactured by JEOL Ltd.), and the average value between the maximum and minimum thicknesses in that field of view is taken as the thickness of the resin coating layer. Five fields of view are measured.

[0097] (Resistance adjuster) The coating resin preferably contains at least one of carbon black, magnesium oxide, and titanium dioxide as a resistance adjusting agent from the viewpoint of adjusting the static resistance value of the carrier. Among these, carbon black is particularly preferred from the viewpoint of its easiness of dispersion in the resin.

[0098] (Exposed area ratio) The charge of the carrier particles is also released through the core particles exposed on the carrier surface. Therefore, when the exposed area ratio of the core particles is 1% or more, the charge is appropriately released from the carrier particles, and excessive charging of the carrier particles can be suppressed. Also, when the exposed area ratio is less than 10%, the resin covering the carrier particles is not easily peeled off when friction occurs between the carrier particles, and the carrier particles are not easily deteriorated.

[0099] For the reasons mentioned above, it is preferable that the exposed area ratio of the core particle on the surface of the carrier particle is within the range of 1.0 to less than 10.0% of the surface area of ​​the core particle, from the viewpoint of suppressing excessive charging of the carrier particle and suppressing deterioration of the carrier particle.

[0100] The exposed area ratio of the core particles to the surface of the carrier particle can be measured, for example, by the following method.

[0101] The measurement device used is "K-Alpha" (manufactured by Thermo Fisher Scientific).

[0102] The main element constituting the coating layer (usually carbon) and the main element constituting the core particle (usually iron) are measured by XPS measurement (X-ray photoelectron spectroscopy measurement). At this time, as the X-ray source, an Al monochromatic X-ray is used, and the acceleration voltage is set to 7 kV and the emission current is set to 6 mV.

[0103] When the core particles are made of iron oxide, the C1s spectrum is measured for carbon, the Fe2p3 / 2 spectrum is measured for iron, and the O1s spectrum is measured for oxygen.

[0104] The number of carbon, oxygen, and iron elements (represented as "AC," "AO," and "AFe," respectively) are determined, and the iron content of the core particle alone and the iron content of the carrier after the core particle is coated with the coating layer are determined based on the obtained carbon, oxygen, and iron element number ratios in the following formula (2) by substituting them into the following formula.

[0105] (Formula 2) Iron content rate [atomic%]=AFe / (AC+AO+AFe)×100

[0106] The coverage ratio is calculated by substituting the iron content of the core particle alone and the iron content of the carrier after the core particle is covered with the coating layer into the following formula (3).

[0107] (Formula 3) Coverage rate [%] = {1-(iron content of carrier) / (iron content of core particle alone)} x 100

[0108] When a material other than iron oxide is used as the core particle, the coverage can be obtained by measuring the spectrum of the metal elements that make up the core particle in addition to oxygen and performing a similar calculation according to the above formula.

[0109] (Method of producing coating resin) The method for producing the coating resin is not particularly limited, and a conventionally known polymerization method can be appropriately used. For example, a pulverization method, an emulsion dispersion method, a suspension polymerization method, a solution polymerization method, a dispersion polymerization method, an emulsion polymerization method, an emulsion polymerization aggregation method, and other known methods can be used. In particular, from the viewpoint of controlling the particle size, it is preferable to synthesize the resin by the emulsion polymerization method.

[0110] The polymerization initiator, surfactant, and further chain transfer agent used as necessary in the emulsion polymerization method are not particularly limited, and conventionally known ones can be used. Furthermore, the polymerization conditions such as the polymerization temperature are not particularly limited, and conventionally known polymerization conditions can be appropriately used to adjust the polymerization conditions.

[0111] Specifically, it is preferable to carry out emulsion polymerization using various additives described in the Examples below. That is, from the viewpoint of particle size control, it is preferable to carry out emulsion polymerization of the above monomers using sodium dodecyl sulfate as an anionic surfactant, water (ion-exchanged water) as a solvent, and potassium persulfate (KPS) as a polymerization initiator.

[0112] (1.2) Toner for developing electrostatic latent images (1.2.1) Toner base particles The toner base particles constituting the electrostatic latent image developing toner (hereinafter, simply referred to as "toner") contained in the two-component developer according to the present invention contain, for example, a binder resin and, if necessary, a colorant. In addition, the toner base particles may further contain other components such as a release agent and a charge control agent, if necessary.

[0113] In the present invention, the term "toner particles" refers to toner base particles to which an external additive has been added, and an aggregate of toner particles is called "toner".

[0114] Although the toner base particles can generally be used as they are as toner particles, in the present invention, the toner base particles to which an external additive has been added are used as toner particles. In the following description, when there is no particular need to distinguish between the toner base particles and the toner particles, they are also simply referred to as "toner particles". Hereinafter, each of the constituent materials of the toner base particles according to the present invention will be described in detail.

[0115] (Binding resin) The binder resin constituting the toner base particles is preferably a thermoplastic resin. As such a binder resin, any resin generally used as a binder resin constituting a toner can be used without any particular limitation.

[0116] Examples of the resin include styrene resin, acrylic resin, styrene-acrylic copolymer resin, polyester, silicone resin, olefin resin, amide resin, epoxy resin, and composite resins in which two or more of these resins are chemically bonded. Among them, styrene resin, acrylic resin, styrene-acrylic copolymer resin, and polyester are preferred because they have low viscosity and high sharp melting properties. These resins can be used alone or in combination of two or more. In particular, it is preferred to include crystalline polyester in order to make the toner particles more soluble and to achieve energy saving during fixing.

[0117] In this specification, "crystalline" means that the material has a clear endothermic peak, not a stepwise endothermic change, in differential scanning calorimetry. Specifically, the clear endothermic peak means a peak whose half-width is within 15°C when measured at a heating rate of 10°C / min in differential scanning calorimetry (DSC) described in the examples.

[0118] The crystalline polyester has a portion synthesized from a polyvalent carboxylic acid component and a polyhydric alcohol component. The crystalline polyester may be in the form of a composite resin in which the crystalline polyester is chemically bonded to another resin.

[0119] Examples of polyvalent carboxylic acid components include aliphatic dicarboxylic acids such as oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, dodecanedioic acid (1,12-dodecanedicarboxylic acid), 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid.

[0120] Other examples include aromatic dicarboxylic acids such as dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, malonic acid, and mesaconic acid. Further examples include, but are not limited to, their anhydrides and their lower alkyl esters. These may be used alone or in combination of two or more.

[0121] Examples of trivalent or higher carboxylic acids include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and the like, as well as their anhydrides and lower alkyl esters, etc. These may be used alone or in combination of two or more.

[0122] In addition to the polyvalent carboxylic acid component, a dicarboxylic acid component having a double bond may be used. Examples of dicarboxylic acids having a double bond include, but are not limited to, maleic acid, fumaric acid, 3-hexenedioic acid, and 3-octenedioic acid. In addition, lower esters and acid anhydrides of these may also be used.

[0123] On the other hand, as the polyhydric alcohol component, an aliphatic diol is preferred, and a straight-chain aliphatic diol having a carbon number in the main chain within the range of 7 to 20 is more preferred. When the aliphatic diol is a straight-chain type, the crystallinity of the polyester is maintained and the drop in melting temperature is suppressed, so that the toner blocking resistance, image storage stability, and low-temperature fixability are excellent. In addition, when the carbon number is within the range of 7 to 20, the melting point during polycondensation with the polybasic carboxylic acid component is suppressed low, low-temperature fixation is realized, and the material is easy to obtain in practice. The carbon number in the main chain is more preferably within the range of 7 to 14.

[0124] Examples of aliphatic diols suitable for use in the synthesis of crystalline polyester include, but are not limited to, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, and 1,18-octadecanediol. These may be used alone or in combination of two or more. Among these, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred in terms of availability.

[0125] Examples of trihydric or higher alcohols include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. These may be used alone or in combination of two or more.

[0126] The crystalline polyester may be synthesized by carrying out a polycondensation reaction between a polyvalent carboxylic acid component and a polyhydric alcohol component in the presence of a polymerization catalyst such as dibutyltin oxide or tetrabutoxytitanate, according to a conventional method. The reaction temperature in the polycondensation reaction is preferably within the range of 180 to 230°C.

[0127] If necessary, the reaction system is decompressed and the reaction is carried out while removing water and alcohol generated by polycondensation. If the monomer is not soluble or compatible at the reaction temperature, a high-boiling point solvent may be added as a solubilizing agent to dissolve the monomer. The polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed with the monomer, and then polycondensed with the main component.

[0128] From the viewpoint of good low-temperature fixability and image storage stability, the weight average molecular weight of the crystalline polyester is preferably within the range of 5000 to 50000. In this specification, the weight average molecular weight of the crystalline polyester is a value measured by GPC, and can be measured under the same measurement conditions as those of the coating resin.

[0129] Examples of polymerizable monomers for obtaining binder resins other than crystalline polyesters (hereinafter also referred to as "other resins") include styrene monomers such as styrene, methylstyrene, methoxystyrene, butylstyrene, phenylstyrene, and chlorostyrene.

[0130] In addition, acrylic acid ester monomers such as methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, and n-stearyl acrylate can be used. In addition, methacrylic acid ester monomers such as methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, and 2-ethylhexyl methacrylate can be used. In addition, carboxylic acid monomers such as acrylic acid, methacrylic acid, and fumaric acid can be used. These polymerizable monomers can be used alone or in combination of two or more kinds.

[0131] These other resins can be produced by known methods such as suspension polymerization, emulsion polymerization, and dispersion polymerization. Among them, emulsion polymerization is preferred from the viewpoint of controlling particle size. When producing other resins by emulsion polymerization, for example, a radical polymerization initiator and a chain transfer agent are used.

[0132] Examples of the radical polymerization initiator include persulfates such as potassium persulfate and ammonium persulfate, water-soluble azo compounds such as 4,4'-azobis(4-cyanovaleric acid) and 2,2'-azobis(2-amidinopropane) hydrochloride, and hydrogen peroxide. The radical polymerization initiator can be used as a redox polymerization initiator as desired, and these can also be used in combination. Examples of combinations include combinations of persulfates and sodium metabisulfite, sodium sulfite, hydrogen peroxide and ascorbic acid, etc.

[0133] Examples of the chain transfer agent include thiol compounds such as n-dodecyl mercaptan, tert-dodecyl mercaptan, and n-octyl mercaptan, as well as halogenated methanes such as tetrabromomethane and tribromochloromethane.

[0134] From the viewpoint of low-temperature fixability and image storage stability, the weight-average molecular weight of the other resin is preferably within the range of 10,000 to 50,000. The weight-average molecular weight of the other resin is a value measured by GPC, and can be measured under the same measurement conditions as those of the coating resin.

[0135] (External additives) An external additive is attached to the surface of the toner base particle according to the present invention in order to control the fluidity and chargeability. As the external additive, conventionally known metal oxide particles can be used. For example, silica particles, titania particles, alumina particles, zirconia particles, zinc oxide particles, chromium oxide particles, cerium oxide particles, antimony oxide particles, tungsten oxide particles, tin oxide particles, tellurium oxide particles, manganese oxide particles, boron oxide particles, strontium titanate particles, calcium titanate particles, magnesium titanate particles, etc. can be mentioned. These may be used alone or in combination of two or more kinds.

[0136] In particular, it is more preferable to use silica particles produced by a sol-gel method. Silica particles produced by a sol-gel method are characterized by a narrow particle size distribution, and are therefore preferable in terms of suppressing variation in adhesion strength. The number-average primary particle size of the silica particles formed by the sol-gel method is preferably within the range of 70 to 150 nm.

[0137] Silica particles having a number-average primary particle size within this range have a larger particle size than other external additives, and therefore act as a spacer, preventing other external additives having smaller particle sizes from being embedded in the toner base particles when stirred and mixed in the developing machine, and also preventing the toner base particles from fusing together.

[0138] The number average primary particle diameter of metal oxide particles other than silica particles produced by the sol-gel method is preferably within a range of 10 to 70 nm, more preferably within a range of 10 to 40 nm. The number average primary particle diameter of metal oxide particles can be measured, for example, from images taken by a scanning electron microscope.

[0139] Furthermore, organic fine particles such as homopolymers of styrene, methyl methacrylate, etc. or copolymers thereof may be used as an external additive, or organic-inorganic composite fine particles obtained by combining the above polymers with inorganic fine particles may be used.

[0140] The metal oxide particles used as the external additive are preferably those whose surfaces have been subjected to hydrophobic treatment with a known surface treatment agent such as a coupling agent, etc. Preferred examples of the surface treatment agent include dimethyldimethoxysilane, hexamethyldisilazane (HMDS), methyltrimethoxysilane, isobutyltrimethoxysilane, and decyltrimethoxysilane.

[0141] Silicone oil can also be used as the surface treatment agent. Specific examples of silicone oil include organosiloxane oligomers, cyclic compounds such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, tetramethylcyclotetrasiloxane, and tetravinyltetramethylcyclotetrasiloxane, and linear or branched organosiloxanes.

[0142] In addition, silicone oils having high reactivity and at least terminals modified by introducing modified groups to the side chain, one end, both ends, one end of the side chain, both ends of the side chain, etc. may be used. Examples of modified groups include, but are not limited to, alkoxy groups, carboxyl groups, carbinol groups, higher fatty acid modified groups, phenol groups, epoxy groups, methacryl groups, and amino groups. In addition, silicone oils having several modified groups such as amino / alkoxy modified groups may be used.

[0143] Dimethyl silicone oil may be mixed with the modified silicone oil and / or other surface treatment agents, such as silane coupling agents, titanate coupling agents, aluminate coupling agents, various silicone oils, fatty acids, fatty acid metal salts, esters thereof, rosin acid, etc.

[0144] In order to further improve the cleaning property and the transfer property, it is possible to use a lubricant as an external additive. Specific examples of the lubricant include salts of higher fatty acids such as zinc stearate and calcium stearate, and boron nitride.

[0145] The amount of these external additives added is preferably within a range of 0.1 to 10% by mass, and more preferably within a range of 1 to 5% by mass, based on the total amount of the toner particles.

[0146] (Release agent) The toner particles may contain a release agent. The release agent is not particularly limited. For example, hydrocarbon waxes such as polyethylene wax, oxidized polyethylene wax, polypropylene wax, oxidized polypropylene wax, and Fischer-Tropsch wax may be mentioned. In addition, known ones such as carnauba wax, fatty acid ester wax, sazol wax, rice wax, candelilla wax, jojoba oil wax, and beeswax wax may be mentioned. The content of the release agent in the toner particles is preferably within a range of 1 to 30 parts by mass, more preferably within a range of 5 to 20 parts by mass, relative to 100 parts by mass of the binder resin.

[0147] (Charge control agent) The toner particles may contain a charge control agent. Examples of the charge control agent include a metal complex of a salicylic acid derivative with zinc or aluminum (salicylic acid metal complex). Other examples include a calixarene compound, an organic boron compound, and a fluorine-containing quaternary ammonium salt compound. The content of the charge control agent in the toner particles is preferably within a range of 0.1 to 5 parts by mass with respect to 100 parts by mass of the binder resin.

[0148] (Coloring agent) The toner particles may further contain a colorant to make the toner a color toner. Usable colorants include known inorganic or organic colorants. Specific colorants are shown below.

[0149] Examples of black colorants include carbon black such as furnace black, channel black, acetylene black, thermal black, lamp black, etc. Also included are magnetic powders such as magnetite and ferrite.

[0150] Examples of colorants for magenta or red include CI Pigment Red 2, 3, 5, 6, 7, 15, 16, 48:1, 48:2, 48:3, 53:1, 57:1, 60, 63, 64, 68, 81, 83, 87, 88, 89, 90, 112, 114, 122, 123, 139, 144, 149, 150, 163, 166, 170, 177, 178, 184, 202, 206, 207, 209, 222, 238, and 269.

[0151] Examples of colorants for orange or yellow include CI Pigment Orange 31, CI Pigment Orange 43, CI Pigment Yellow 12, 14, 15, 17, 74, 83, 93, 94, 138, 155, 162, 180, and 185.

[0152] Examples of colorants for green or cyan include CI Pigment Blue 2, 3, 15, 15:2, 15:3, 15:4, 16, 17, 60, 62, 66, CI Pigment Green 7, and the like.

[0153] Examples of dyes include CI Solvent Red 1, 49, 52, 58, 63, 111, and 122, CI Solvent Yellow 2, 6, 14, 15, 16, 19, 21, 33, 44, 56, 61, 77, 79, 80, 81, 82, 93, 98, 103, 104, 112, and 162, CI Solvent Blue 25, 36, 60, 70, 93, and 95.

[0154] These colorants may be used alone or in combination as necessary. When a colorant is used, the amount of the colorant added is preferably within a range of 1 to 30% by mass, more preferably within a range of 2 to 20% by mass, based on the total mass of the toner.

[0155] The colorant may be surface-modified. As the surface modifier, a conventionally known one may be used, and specifically, a silane coupling agent, a titanium coupling agent, an aluminum coupling agent, etc. may be preferably used.

[0156] (others) [Volume average particle size] The toner particles according to the present invention have a volume average particle size in the range of 3 to 10 μm. If the volume average particle size is less than 3 μm, the fluidity of the toner particles decreases, and the charge build-up of the toner particles decreases. On the other hand, if it exceeds 10 μm, a decrease in image quality occurs. The toner particles preferably have a volume average particle size in the range of 3.5 to 6.5 μm. The volume average particle size of the toner particles is specifically determined by the volume-based median diameter (D 50 ) shall be adopted.

[0157] The volume-based median diameter of toner particles (D 50 ) can be measured and calculated using a device that connects a computer system for data processing to a Multisizer 3 (manufactured by Beckman Coulter).

[0158] The measurement procedure involves mixing 0.02 g of toner particles with 20 mL of surfactant solution, then ultrasonically dispersing for 1 minute to prepare a toner particle dispersion. Note that the surfactant solution may be, for example, a surfactant solution prepared by diluting a neutral detergent containing a surfactant component 10 times with pure water for the purpose of dispersing the toner particles.

[0159] This toner particle dispersion is pipetted into a beaker containing ISOTON II (manufactured by Beckman Coulter) in the sample stand until the measurement concentration is within the range of 5 to 10%. Then, the measurement is performed by setting the measurement count to 25,000 particles. The aperture diameter of the Multisizer 3 used is 100 μm.

[0160] The measurement range of 1 to 30 μm was divided into 256 parts to calculate the frequency, and the particle size of 50% of the largest volume fraction was determined as the volume-based median diameter (D 50 )

[0161] The volume average particle size of the toner particles can be controlled by controlling the concentration of the coagulant, the amount of the organic solvent added, or the fusion time in the above-mentioned production method.

[0162] [Average circularity] The average circularity of the toner particles according to the present invention is preferably 0.98 or less, and more preferably 0.930 to 0.975. If the average circularity is within such a range, the toner particles become more easily charged. The average circularity can be measured, for example, using a flow type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation), and specifically, it can be measured by the following method.

[0163] The toner particles are wetted with a surfactant solution and dispersed by ultrasonic dispersion for 1 minute. Then, using the "FPIA-3000", measurements are taken at an appropriate concentration of 3,000 to 10,000 HPF detections in HPF (high magnification imaging) mode. Within this range, reproducible measurements can be obtained. The circularity is calculated using the following formula (5).

[0164] Equation (5) Circularity = (perimeter of a circle with the same projected area as the particle image) / (perimeter of the particle projected image)

[0165] The average circularity is the arithmetic mean value obtained by adding up the circularity of each particle and dividing the sum by the total number of particles measured.

[0166] The average circularity of the toner particles can be controlled by controlling the temperature, time, etc. during the aging treatment in the above-mentioned production method.

[0167] (1.2.2) Toner manufacturing method The toner base particles according to the present invention, i.e., particles at a stage before adding external additives, can be manufactured by a known toner manufacturing method. That is, a so-called pulverization method in which toner base particles are manufactured through kneading, pulverization, and classification processes, and a so-called polymerization method in which polymerizable monomers are polymerized and particles are formed while controlling the shape and size at the same time, can be mentioned. Toner particles are manufactured by adding external additives to the toner base particles and mixing them.

[0168] As a mixer for the external additives, various known mixers such as a Turbula mixer, a Henschel mixer, a Nauta mixer, a V-type mixer, etc. For example, when using a Henschel mixer, the peripheral speed of the tip of the stirring blade is preferably set within a range of 30 to 80 m / s, and the mixture is stirred and mixed for about 10 to 30 minutes within a range of 20 to 50°C.

[0169] 2.Photoreceptor The term "photoreceptor" refers to an object that carries a latent or visible image on its surface in an electrophotographic image forming method. The photoreceptor according to the present invention is composed of, for example, a support, a photosensitive layer, a protective layer and other layers.

[0170] In image formation, the surface of the photoconductor is first charged to create a potential difference between it and the support surface. Next, an exposure device generates charges from the photosensitive layer, which cancel out the charges on the photoconductor surface, forming an electrostatic latent image on the photoconductor surface. Next, a development bias voltage is applied to the developer carrier, which electrostatically attracts toner from the developer carrier to the latent image area on the photoconductor surface, developing it.

[0171] (2.1) Support The support of the photoreceptor according to the present invention is an electrically conductive support made of an aluminum alloy.

[0172] (Silicon content) The silicon content in the aluminum alloy is in the range of more than 0.6% by mass and not more than 12.6% by mass. The aluminum alloy may contain other elements in addition to silicon, such as copper, chromium, nickel, and zinc. If the silicon content in the aluminum alloy is 0.6% by mass or less, the processability is reduced, resulting in an uneven surface of the photoreceptor. In addition, if the silicon content in the aluminum alloy is more than 12.6% by mass, coarse crystals (protrusions) due to the eutectic of silicon and aluminum are likely to occur.

[0173] From the viewpoint of the processability of the surface of the support of the photoreceptor, the silicon content in the aluminum alloy is more preferably more than 0.8 mass %.

[0174] [Measurement method] The silicon content in an aluminum alloy is obtained by measuring the amount of silicon, which can be measured, for example, by inductively coupled plasma optical emission spectroscopy. Inductively coupled plasma optical emission spectroscopy is a method in which a solution sample in which metal is dissolved in acid or alkali is sprayed into Ar plasma, the excited light is separated into individual wavelengths, and the type and amount of element are quantified from the light intensity. With this method, there is a linear relationship between light intensity and amount from trace to high concentration, and each element can be analyzed simultaneously.

[0175] As a measuring device for high-frequency inductively coupled plasma optical emission spectrometry, for example, the "ULTIMA2000 (manufactured by Horiba, Ltd.)" can be used. In addition, optical emission spectrometry with an argon atmosphere discharge optical emission stand, optical emission spectrometry with an atmospheric discharge optical emission stand, glow discharge mass spectrometer (GD-MS), X-ray fluorescence spectrometer (XRF), etc. can also be used.

[0176] When a coating layer such as a resin layer is present on the support of the photoreceptor according to the present invention, the measurement is carried out after the coating layer such as the resin layer is appropriately removed with a solvent or the like.

[0177] (2.2) Photosensitive layer The photosensitive layer is a layer for forming an electrostatic latent image of a desired image on the surface of the photoreceptor by an exposure means described later. The photosensitive layer may be a single layer or may be composed of a plurality of laminated layers. Preferred examples of the photosensitive layer include a single layer containing a charge transport material and a charge generating material, and a laminate of a charge transport layer containing a charge transport material and a charge generating layer containing a charge generating material.

[0178] (2.3) Protective layer The protective layer is a layer for improving the mechanical strength of the photoreceptor surface and improving scratch resistance and abrasion resistance. A preferred example of the protective layer is a layer containing a polymerized and cured product of a composition containing a polymerizable monomer.

[0179] (2.4) Other layers The photoreceptor may further include layers other than the above-mentioned conductive support, photosensitive layer, and protective layer.

[0180] (2.4.1) Middle Tier A preferred example of the other layer is an intermediate layer, etc. The intermediate layer is, for example, a layer that has a barrier function and an adhesive function and is disposed between the conductive support and the photosensitive layer.

[0181] (2.4.2) Outermost layer In this specification, the outermost layer of the photoreceptor refers to a layer disposed at the outermost side on the side that comes into contact with the toner. The outermost layer is not particularly limited, but is preferably the above-mentioned protective layer. In the photoreceptor according to the present invention, the outermost layer preferably contains inorganic particles, and more preferably the inorganic particles are surface-treated with a surface treatment agent. Examples of the surface treatment agent include a silane coupling agent, an electron transporting compound, and a compound having a polymerizable functional group. The thickness of the outermost layer is preferably within a range of 1 to 10 μm, and more preferably within a range of 1.5 to 5 μm.

[0182] (Inorganic particles) The inorganic particles are not particularly limited, and examples thereof include titanium oxide, zinc oxide, alumina (aluminum oxide), silica (silicon oxide), tin oxide, antimony oxide, indium oxide, bismuth oxide, magnesium oxide, lead oxide, tantalum oxide, yttrium oxide, cobalt oxide, copper oxide, manganese oxide, selenium oxide, iron oxide, zirconium oxide, germanium oxide, niobium oxide, molybdenum oxide, vanadium oxide, tin-doped indium oxide, antimony-doped tin oxide and zirconium oxide, and copper-aluminum composite oxide (CuAlO 2 ) are included.

[0183] The inorganic particles preferably contain at least one of tin, zinc, titanium, silicon and copper, more preferably contain at least one of tin, zinc, titanium and copper, and particularly preferably contain at least one of tin, zinc and copper.

[0184] The number average primary particle size of the inorganic particles is not particularly limited, but is preferably within the range of 5 to 300 nm, and more preferably within the range of 10 to 200 nm.

[0185] The number average primary particle size of the inorganic particles can be calculated from the average length of the major axis of particle images observed under a scanning electron microscope.

[0186] (Binding resin) The outermost layer (protective layer) may contain a binder resin. As the binder resin for the outermost layer, a known binder resin can be used.

[0187] (2.5) Photoreceptor manufacturing method The photoreceptor according to the present invention can be manufactured by a known method for manufacturing an electrophotographic photoreceptor. It is preferable to manufacture the photoreceptor by a method including a step of applying an outermost layer forming coating liquid containing inorganic particles to the surface of a photosensitive layer formed on an aluminum alloy support. In addition, it is preferable to manufacture the photoreceptor by a method including a step of irradiating the applied outermost layer forming coating liquid with active energy rays or heating the applied outermost layer forming coating liquid to obtain a cured product of the outermost layer forming composition.

[0188] 3. Developer carrier The silicon content in the aluminum alloy forming the developer carrier according to the present invention is in the range of more than 0.6 mass % and not more than 12.6 mass %.

[0189] If there are protrusions of a certain size or more on the surface of the developer carrier, a charge leak occurs between the protrusions and the surface of the photoconductor when a toner image is formed on a recording medium. The absolute value of the electric potential decreases at the points on the surface of the developer carrier where the charge leaks, and as a result, toner is no longer attracted to the points where the charge leaks. The points where toner is no longer attracted are called "white spots," and because the toner is not applied to the recording medium, this is considered a localized image defect.

[0190] In order to suppress the leakage of charge from the surface of the developer carrier according to the present invention, it is necessary to set the absolute value of the potential when the voltage is applied small. However, if the absolute value of the potential when the development bias voltage is applied is set small, the toner becomes difficult to separate from the photoconductor, which may result in a decrease in image density, particularly in a low-temperature, low-humidity environment where the toner charge amount is likely to be high.

[0191] However, the static resistance is 1.0×10 12 ~5.0×10 14 By using the above-mentioned carrier within the Ω·cm range in a two-component developer, it is possible to prevent the charge amount of the toner from increasing and suppress the decrease in image density as described above.

[0192] (Configuration of Developer Carrier) The developer carrier according to the present invention is composed of, for example, a developing sleeve, a flange, a shaft, and a magnet roller. The above-mentioned "developing sleeve" is a means having a function of carrying a moderately charged developer and supplying the developer to a photoconductor on which an electrostatic latent image is formed, and is, for example, a part of a developer carrier of a developing device provided in an electrophotographic image forming apparatus.

[0193] However, a developer carrier having a "developing sleeve" as part of its configuration does not have to include a magnet portion such as a magnet roller as part of its configuration. Also, the shape of the developing sleeve is not a simple cylindrical shape as disclosed in JP-A-2003-91084, and does not include tube-like shapes with lotus-root-shaped holes in the cross section.

[0194] Fig. 1 is an external view of a developer carrier. For example, the developing sleeve 11 in Fig. 1 is rotatable and cylindrical, and plays a role of carrying and transporting the developer on its surface. Note that the surface of the developing sleeve 11 is not limited to the configuration shown in Fig. 1, and for example, grooves or the like may be formed on the surface.

[0195] 2 and 3 are examples of axial cross-sectional views of the developer carrier of the present invention, each of which has a magnet roller and a shaft having a different shape. The developer carrier of the present invention does not need to include a magnet portion such as a magnet roller as part of its configuration, and is not limited to the configurations of FIGS. 2 and 3.

[0196] 2 is a cross-sectional view of a developer carrier in which the shaft does not pass through the magnet roller. As shown in Fig. 2, the developer carrier 10 has a shaft 16 fixed by inserting the shaft into a hole formed in the magnet roller 12, and is provided with a developing sleeve 11 made of a non-magnetic material on the outer periphery of the magnet roller 12.

[0197] 3 is a cross-sectional view of a developer carrier in which a shaft passes through a magnet roller. As shown in FIG. 3, the developer carrier 10 has a magnet roller 12 fixed around a shaft 16 and a developing sleeve 11 made of a non-magnetic material attached to the outer periphery of the magnet roller 12.

[0198] The developing sleeve 11 is connected to the magnet roller 12 with a predetermined gap therebetween via a bearing portion 17 such as a bearing provided on the outside of the magnet roller 12 .

[0199] Outside the axial bearing portion 17 of the developing sleeve 11, a counter-driving side flange 18 and a driving side flange 19 are connected to the developing sleeve 11. The counter-driving side flange 18 and the driving side flange 19 may be reversed, and are not limited to this. The counter-driving side flange 18 and the driving side flange 19 are rotated together with the developing sleeve 11 while being held by the developing container.

[0200] (Silicon content) The silicon content in the aluminum alloy forming the developer carrier according to the present invention is in the range of more than 0.6 mass % to 12.6 mass % or less. The aluminum alloy forming the developer carrier according to the present invention does not include the materials forming the flange, shaft, and magnet roller (see Figures 1, 2, and 3).

[0201] If the silicon content in the aluminum alloy is 0.6% by mass or less, the workability is reduced, the surface of the developer carrier becomes uneven, and unevenness occurs in the image. If the silicon content in the aluminum alloy is more than 12.6% by mass, the strength increases, but coarse crystals (protrusions) due to the eutectic of silicon and aluminum are likely to occur. Therefore, it is not possible to impart appropriate roughness to the surface of the developing sleeve of the developer carrier, resulting in poor image quality (white spots).

[0202] From the viewpoint of the processability of the surface of the developer-carrying member according to the present invention, the silicon content in the aluminum alloy is more preferably more than 0.8% by mass.

[0203] [Measurement method] The method for measuring the silicon content in the aluminum alloy is the same as the method for measuring the silicon content in the aluminum alloy in the support of the photoreceptor described above.

[0204] (surface) From the viewpoint of imparting an appropriate roughness to the surface of the developing sleeve of the developer carrier, sandblasting is preferred, which makes it possible to maintain the outer peripheral surface of the developing sleeve at an appropriate roughness.

[0205] 4.Image forming method The image forming method of the present invention is an image forming method using a two-component developer and an image forming apparatus equipped with at least one of a photoreceptor using an aluminum alloy support or a developer carrier made of an aluminum alloy, wherein the static resistance value of the carrier contained in the two-component developer is 1.0×10 12 ~5.0×10 14 The aluminum alloy forming at least the photoreceptor support or the developer carrier has a silicon content of more than 0.6 mass % and not more than 12.6 mass %, and can be suitably used in the image forming system of the present invention.

[0206] 5. Image forming equipment In the image forming method of the present invention, for example, the following image forming apparatus can be used, and the image forming apparatus is equipped with a charging unit, an exposing unit, a developing unit, and a transferring unit. The image forming apparatus is equipped with the above-mentioned photoconductor and developer carrier.

[0207] Fig. 4 is an explanatory cross-sectional view showing an example of the configuration of an image forming apparatus according to the present invention. The image forming apparatus 100 shown in Fig. 4 is called a tandem type color image forming apparatus, and has four image forming units 110Y, 110M, 110C, and 110Bk, a paper feed conveying means 150, and a fixing means 170.

[0208] An original image reading device SC is disposed on the upper portion of the main body of the image forming apparatus 100.

[0209] The image forming units 110Y, 110M, 110C, and 110Bk are arranged side by side in the vertical direction.

[0210] The image forming units 110Y, 110M, 110C, and 110Bk each include a rotating drum-shaped photoconductor 111Y, 111M, 111C, and 111Bk, charging means 113Y, 113M, 113C, and 113Bk, exposure means 115Y, 115M, 115C, and 115Bk, developing means 117Y, 117M, 117C, and 117Bk, primary transfer rollers (primary transfer means) 133Y, 133M, 133C, and 133Bk, and cleaning means 119Y, 119M, 119C, and 119Bk, which are arranged sequentially in the rotational direction of the photoconductor in the outer circumferential surface area.

[0211] The photoreceptor uses an aluminum alloy support, and the silicon content in the aluminum alloy is in the range of more than 0.6 mass % and not more than 12.6 mass %.

[0212] A configuration is adopted in which toner images of yellow (Y), magenta (M), cyan (C) and black (Bk) are formed on the photoconductors 111Y, 111M, 111C and 111Bk, respectively.

[0213] In the following description, the image forming unit 110Y will be taken as an example when referring to the drawings.

[0214] <Charging means> The charging means is a means for uniformly charging the surface of the photoreceptor. There are contact types of charging means such as charging rollers, charging brushes, and charging blades, and non-contact types such as corona chargers (corotron chargers, strocotton chargers, etc.). The contact type has the advantage of generating less harmful ozone gas during the charging process. The non-contact type has the advantage of being less prone to filming, since it is not a close-proximity discharge, as compared to the contact type.

[0215] The charging means provided in the image forming system of the present invention may be of a contact type or a non-contact type.

[0216] It is preferable that the charging means is a proximity charging roller or a contact charging roller, since this reduces the amount of harmful ozone gas generated during the charging process and is advantageous for achieving high image quality and miniaturization of the apparatus.

[0217] 4 is of a contact type. The charging unit 113Y in this example is made up of a charging roller arranged in contact with the surface of the photoconductor 111Y, and a power source that applies a voltage to the charging roller.

[0218] <Exposure means> The exposure means is a means for exposing the photoconductor, which has been given a uniform potential by the charging means, based on an image signal to form an electrostatic latent image corresponding to the image. Examples of the exposure means include those consisting of LEDs and imaging elements in which light emitting elements are arranged in an array in the axial direction of the photoconductor, and those consisting of a laser optical system.

[0219] <Developing method> The developing means (developing machine) is a means for supplying a developer to the surface of the photoconductor to develop the electrostatic latent image formed on the surface of the photoconductor and form a toner image. The developer used is a developer containing the above-mentioned toner and carrier. The static resistance value of the carrier is 1.0×10 12 ~5.0×10 14 It is in the range of Ω·cm.

[0220] The developing means may be provided with a lubricant supplying means for supplying a lubricant to the developer, and it is preferable that the developer supplied by the developing means contains a lubricant from the viewpoint of improving abrasion resistance. It is more preferable that the lubricant is a metal soap from the viewpoint of improving abrasion resistance.

[0221] The developing means 117Y shown in FIG. 4 is specifically composed of a developer carrier 118Y that incorporates a magnet roller and rotates while holding a developer, and a voltage application device (not shown) that applies a DC and / or AC bias voltage between the photoconductor 111Y and the developer carrier 118Y.

[0222] The developer carrier is composed of the developing sleeve, the flange, the shaft, and the magnet roller as described above. The silicon content of the aluminum alloy contained in the developer carrier is in the range of more than 0.6% by mass and not more than 12.6% by mass.

[0223] The developer is transported to the photoconductor 111Y by the rotation of the developer carrier 118Y. Then, a thin layer of toner on the developer carrier 118Y comes into contact with the photoconductor 111Y to develop the electrostatic latent image on the photoconductor 111Y.

[0224] The developer carrier 118Y is connected to a voltage application device. This voltage application device applies a DC and / or AC bias voltage to the developer carrier 118Y. The developer carrier 118Y is configured to be able to adjust the development bias to a desired value by controlling the voltage applied to the developer carrier 118Y.

[0225] An electric field is formed in a development section where the developer carrier 118Y and the photoconductor 111Y face each other due to a potential difference (development potential difference) between the developer carrier 118Y and the potential of the electrostatic latent image carried by the photoconductor 111Y. The toner in the developer transported to the development section by the rotation of the developer carrier 118Y moves due to the force exerted by the electric field, and is attracted to the electrostatic latent image on the photoconductor 111Y. The electrostatic latent image carried by the photoconductor 111Y is visualized, and a toner image corresponding to the shape of the electrostatic latent image is formed on the surface of the photoconductor 111Y.

[0226] [Development potential difference] The "development potential difference" is the difference between the potential (Vi) of the image area and the development potential (Vdc). It is preferable that the absolute value of the development potential difference is within a range of 300 to 800 V from the viewpoints of suppressing the occurrence of charge leakage and ensuring image density.

[0227] <Transfer Method> The transfer means is a means for transferring a toner image onto a recording medium. When an intermediate transfer body is used, the primary transfer roller serves as the transfer means.

[0228] 4 transfers the toner image formed on the photoconductor 111Y onto the endless belt-like intermediate transfer body 131. The primary transfer roller 133Y is disposed in contact with the intermediate transfer body 131.

[0229] In the image forming apparatus 100 shown in FIG. 4, an intermediate transfer method is adopted in which the toner images formed on the photoconductors 111Y, 111M, 111C, and 111Bk are transferred to the intermediate transfer body 131 by primary transfer rollers (primary transfer means) 133Y, 133M, 133C, and 133Bk, and each toner image transferred to the intermediate transfer body 131 is transferred to the transfer material P by a secondary transfer roller (secondary transfer means) 217, but a direct transfer method may also be adopted in which the toner images formed on the photoconductors are transferred directly to the transfer material P by a transfer means. EXAMPLES

[0230] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified.

[0231] A. Preparation of each photoreceptor (A.1) Preparation of photoreceptor 1 Photoreceptor 1 was prepared according to the following procedure.

[0232] (Preparation of conductive support) A conductive support made of an aluminum alloy was prepared. The silicon content relative to the total amount of the aluminum alloy is 0.7 mass %. The conductive support has an outer diameter of 30 mm and a length of 360 mm.

[0233] (Formation of the intermediate layer) Next, the following component [1] was dispersed in the amounts shown below to prepare a coating liquid for forming an intermediate layer.

[0234] <Ingredient [1]> Polyamide resin 1.0 parts by weight Titanium oxide 1.1 parts by mass Ethanol 15 parts by weight

[0235] At this time, a sand mill was used as the dispersing machine for component (1), and dispersion was carried out for 10 hours in a batch manner.

[0236] The polyamide resin of the above component [1] used as the binder resin is "X1010" (manufactured by Daicel Degussa Corp.) The titanium oxide of the component [1] used as the conductive particles is "SMT500SAS" (manufactured by Teika Corp.) and has a number average primary particle diameter of 0.035 μm.

[0237] The coating solution for forming the intermediate layer, which was prepared by dispersing component [1], was applied to the outer peripheral surface of the conductive support by dip coating, and then dried in an oven at 110°C for 20 minutes. As a result, an intermediate layer having a thickness of 2 μm was formed on the surface of the conductive support.

[0238] (Formation of Charge Generation Layer) Next, the following component [2] was mixed in the amounts shown below to prepare a coating solution for the charge generating layer.

[0239] <Ingredient [2]> Mixed crystal of adduct A and charge generating substance 24 parts by mass Polyvinyl butyral resin 12 parts by weight Mixed liquid A 400 parts by mass

[0240] The charge generating substance of the above component [2] is titanyl phthalocyanine, which has clear peaks at 8.3°, 24.7°, 25.1°, and 26.5° in Cu-Kα characteristic X-ray diffraction spectrum measurement. The adduct A of the component [2] is a compound in which (2R,3R)-2,3-butanediol is added to the charge generating substance (the above titanyl phthalocyanine) in a 1:1 ratio.

[0241] The polyvinyl butyral of the above component [2] is "S-LEC BL-1" (manufactured by Sekisui Chemical Co., Ltd.) ("S-LEC" is a registered trademark of the company). The mixed solution A of component [2] is 3-methyl-2-butanone / cyclohexanone = 4 / 1 (V / V).

[0242] At this time, the mixer for component [2] was a circulation type ultrasonic homogenizer "RUS-600TCVP" (manufactured by Nippon Seiki Seisakusho Co., Ltd.) under the following conditions.

[0243] <Condition> The vibration frequency of the circulating ultrasonic homogenizer is 19.5 kHz, the output is 600 W, and the circulation flow rate is 40 L per hour, and dispersion is performed for 0.5 hours.

[0244] The coating solution for the charge generating layer, which was prepared by mixing component [2], was applied to the surface of the intermediate layer by dip coating, and the mixture was naturally dried for 20 minutes to form a charge generating layer having a thickness of 0.3 μm on the surface of the intermediate layer.

[0245] (Formation of charge transport layer) The following components [3] were mixed in the amounts shown below and dissolved to prepare a coating solution [A1] for the charge transport layer.

[0246] <Ingredient [3]> Charge transport material CTM-1 75 parts by mass Polycarbonate 100 parts by weight Antioxidant 4 parts by weight

[0247] The chemical structure of the charge transport material CTM-1 of the above component [3] is shown below.

[0248] [ka]

[0249] The polycarbonate of the above component [3] is "Z300" (manufactured by Mitsubishi Gas Chemical Co., Ltd.). The antioxidant of the above component [3] is "IRGANOX1010" (manufactured by BASF) ("IRGANOX" is a registered trademark of the company).

[0250] The coating solution [A1] for the charge transport layer of the charge generating layer was applied and dried for 70 minutes at 120° C. As a result, a charge transport layer having a thickness of 21 μm was formed on the surface of the charge generating layer.

[0251] (A.2) Preparation of photoreceptors 2 to 5 Photoreceptors 2 to 5 were prepared in the same manner as in the preparation of photoreceptor 1, except that the content of silicon relative to the total amount of aluminum alloy was set to the amount shown in Table I.

[0252] [Table 1]

[0253] B. Preparation of the developer carrier (B.1) Preparation of developer carrier 1 The developer carrying member 1 was prepared according to the following procedure.

[0254] (Making of developing sleeve) [Preparation of Support] A cylindrical support made of an aluminum alloy was prepared. The silicon content of the aluminum alloy of this cylindrical support was 0.5 mass %. This cylindrical support was a thin cylindrical support having an outer diameter of 16 mm, an inner diameter of 15 mm, and a wall thickness of 1 mm.

[0255] [Sandblasting] The developer carrying member was sandblasted on the outer peripheral surface of the cylinder by spraying glass beads with a blast gun, to prepare a developing sleeve. The roughness (Rz) of the sleeve surface was 10 μm.

[0256] The processing conditions for the sandblasting treatment are as follows:

[0257] <Processing conditions> Glass bead type: FGB#80 Glass beads feed rate: 200g / min Distance from blast gun to cylinder: 100mm Blast gun movement speed: 5.0cm / sec Compressed air pressure: 0.23MPa Cylinder rotation speed: 545 rpm

[0258] (Installation of magnetic rollers) A magnet roller was disposed inside the above-mentioned developing sleeve as shown in FIG.

[0259] (B.2) Preparation of Developer Carriers 2 to 5 Developer carriers 2 to 5 were prepared in the same manner as for the developer carrier 1, except that the silicon content in the aluminum alloy was set to the amount shown in Table II.

[0260] [Table 2]

[0261] C. Preparation of the Carrier (C.1) Preparation of coating resin (C.1.1) Preparation of coating resin 1 To an aqueous solution of 0.3 mass % sodium benzenesulfonate, monomers of cyclohexyl methacrylate and styrene were added in a mass ratio of (50:50).

[0262] Potassium peroxodisulfate was added in an amount equivalent to 0.5% by mass of the total amount of the above monomers, and emulsion polymerization was carried out to produce coating resin 1. The weight average molecular weight of this coating resin 1 was measured using a known measuring device and found to be 500,000.

[0263] (C.1.2) Preparation of coating resins 2 to 5 Coating resins 2 to 5 were prepared in the same manner as for coating resin 1, except that the coating layer material was changed as shown in Table III.

[0264] [Table 3]

[0265] (C.1) Preparation of Carrier 1 Carrier 1 was prepared according to the following procedure.

[0266] (Preparation of core particles) The volume average particle size is 35 μm and the saturation magnetization is 61 A m 2 The volume resistivity of the ferrite particles was 4.5×10 7 It was Ωcm.

[0267] (Coating of core particles) 100 parts by mass of the "core particles" prepared above and 3.5 parts by mass of "coating resin 1" were added to a high-speed mixer with stirring blades. At this time, the mixture was mixed and stirred for 15 minutes at 22°C under conditions where the peripheral speed of the horizontal rotor was 8 m / sec. After that, the mixture was mixed at 120°C for 50 minutes to produce carrier 1 having a resin coating layer on the surface of the core particles by the action of mechanical impact force (mechanochemical method). The core exposed area ratio of carrier 1 was 10%, and the volume resistance value was 10 12 The value was Ω·cm.

[0268] (C.2) Preparation of carriers 2 to 7 and 11 to 14 Carriers 2 to 7 and 11 to 14 were prepared in the same manner as in the preparation of Carrier 1, except that the type and amount of the coating resin were changed as shown in Table IV.

[0269] (C.3) Preparation of Carrier 8 100 parts by mass of the "core particles" prepared above and 4.0 parts by mass of "coating resin 1" were added to a high-speed mixer with stirring blades. At this time, carbon black with a particle size of 25 nm (volume resistivity: 1.2 × 10 -1The mixture was mixed and stirred for 15 minutes at 22°C with the horizontal rotor blades at a peripheral speed of 8 m / sec. After that, the mixture was mixed for 50 minutes at 120°C to produce Carrier 8, which has a resin coating layer on the surface of the core particles due to the action of mechanical impact force (mechanochemical method). The exposed core area ratio of Carrier 8 was 8%, and the volume resistivity was 10 12 The value was Ω·cm.

[0270] (C.4) Preparation of Carriers 9 and 10 Carriers 9 and 10 were prepared in the same manner as in the preparation of Carrier 8, except that the resistance adjuster was changed as shown in Table IV.

[0271] [Table 4]

[0272] D. Toner Preparation Only one type of toner was produced, and this toner was designated as Toner 1.

[0273] (D.1) Preparation of amorphous polyester particle dispersion (a1) (D.1.1) Preparation of amorphous polyester (A1) Into a reaction vessel equipped with a stirrer, a thermometer, a condenser, and a nitrogen gas inlet tube, the following monomer [1] and 0.25 parts by mass of "tin dioctylate" per 100 parts by mass of the total of the following monomer [1] were added.

[0274] <Monomer [1]> Bisphenol A ethylene oxide 2.2 mole adduct 40 mole parts Bisphenol A propylene oxide 2.2 mole adduct 60 mole parts Dimethyl terephthalate 60 parts by mole Dodecenyl succinic anhydride 20 mole parts

[0275] The reaction was carried out in a reaction vessel at 235° C. for 6 hours under a nitrogen gas flow. Thereafter, the temperature inside the reaction vessel was lowered to 200° C., and 15 molar parts of dimethyl fumarate and 5 molar parts of trimellitic anhydride were added to the reaction vessel, and the reaction was carried out in the reaction vessel for 1 hour.

[0276] The temperature in the reaction vessel was raised to 220°C over 5 hours, and polymerization was continued under a pressure of 10 kPa until the desired molecular weight was reached, producing a pale yellow transparent amorphous polyester (A1). The amorphous polyester (A1) had a weight average molecular weight (Mw) of 35,000, a number average molecular weight (Mn) of 8,000, and a glass transition temperature (Tg) of 56°C.

[0277] (D.1.2) Preparation of amorphous polyester (A1) particle dispersion Next, the amorphous polyester (A1) and the following mixed solution [2] were placed in a separable flask in the amounts shown below, and thoroughly mixed to dissolve.

[0278] Amorphous polyester (A1) 200.0 parts by mass

[0279] <Mixed solution [2]> Methyl ethyl ketone 100.0 parts by mass Isopropyl alcohol 35.0 parts by weight 10% by weight ammonia aqueous solution 7.0 parts by weight

[0280] Thereafter, while heating and stirring the contents of the separable flask at 40° C., ion-exchanged water was added dropwise at a rate of 8 g / min using a liquid-transfer pump. When the amount of ion-exchanged water delivered reached 580 parts by mass, the addition of ion-exchanged water was stopped. After that, the solvent was removed under reduced pressure to prepare a dispersion liquid (a) of amorphous polyester particles.

[0281] Ion-exchanged water was added to the dispersion (a) to adjust the solid content to 25% by mass, thereby preparing an amorphous polyester particle dispersion (a1). The volume-based median diameter (d50) of the amorphous polyester particles contained in the dispersion (a1) was measured by Microtrac UPA-150 (manufactured by Nikkiso Co., Ltd.) and found to be 156 nm.

[0282] (D.2) Preparation of amorphous vinyl resin particle dispersion (b1) A 5L reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introduction device was charged with 5.0 parts by mass of an anionic surfactant (Dowfax manufactured by Dow Chemical Company) and 2500 parts by mass of ion-exchanged water, and the temperature inside the reaction vessel was raised to 75°C while stirring at a stirring speed of 230 rpm under a nitrogen stream. Next, a solution in which 18.0 parts by mass of potassium persulfate (KPS) was dissolved in 342 parts by mass of ion-exchanged water was added to the reaction vessel, and the liquid temperature was raised to 75°C.

[0283] Further, a mixed solution consisting of the following monomer [3] was added dropwise to the above reaction vessel over a period of 2 hours in the amount shown below.

[0284] <Monomer [3]> Styrene (St) 903.0 parts by mass n-Butyl acrylate (BA) 282.0 parts by mass Acrylic acid (AA) 12.0 parts by mass 1,10-Decanediol diacrylate 3.0 parts by mass Dodecanethiol 8.1 parts by mass

[0285] After the dropwise addition, polymerization was carried out by heating and stirring at 75°C for 2 hours to prepare a dispersion liquid (b) of amorphous vinyl resin particles. Ion-exchanged water was added to this dispersion liquid (b) to adjust the solid content to 25 mass%, and an amorphous vinyl resin particle dispersion liquid (b1) was prepared. The "amorphous vinyl resin" contained in the above-mentioned amorphous vinyl resin particle dispersion liquid (b1) is referred to as "amorphous vinyl resin (B1)".

[0286] The volume-based median diameter (d50) of the amorphous vinyl resin particles contained in the amorphous vinyl resin particle dispersion (b1) was measured with Microtrac UPA-150 (manufactured by Nikkiso Co., Ltd.) and was found to be 160 nm.

[0287] The amorphous vinyl resin (B1) had a glass transition temperature (Tg) of 52° C., a weight average molecular weight (Mw) of 38,000, and a number average molecular weight (Mn) of 15,000.

[0288] (D.3) Preparation of crystalline polyester particle dispersion (c1) (D.3.1) Preparation of crystalline polyester (C1) The following monomer [4] was placed in the following amount into a reaction vessel equipped with a stirrer, a thermometer, a condenser and a nitrogen gas inlet tube, and the atmosphere in the reaction vessel was replaced with dry nitrogen gas.

[0289] <Monomer [4]> Dodecanedioic acid 50 mole parts 1,6-Hexanediol 50 mole parts

[0290] Next, titanium tetrabutoxide (Ti(On-Bu) 4 The temperature inside the reaction vessel was adjusted to 170° C. under a nitrogen gas flow, and the mixture was stirred for 3 hours to carry out the reaction.

[0291] After that, the temperature in the reaction vessel was further increased to 210°C over 1 hour, the pressure in the reaction vessel was reduced to 3 kPa, and the mixture was stirred and reacted under reduced pressure for 13 hours. This resulted in the production of crystalline polyester (C1). The crystalline polyester (C1) had a weight average molecular weight (Mw) of 25,000, a number average molecular weight (Mn) of 8,500, and a melting point of 71.8°C.

[0292] (D.3.2) Mixture of crystalline polyester (C1) with monomer [5] Next, the crystalline polyester (C1) and a mixture of the following mixed solution [5] were placed in a separable flask in the amounts shown below, and the mixture was thoroughly mixed and dissolved at 60°C. After that, 8 parts by mass of a 10% by mass aqueous ammonia solution was added dropwise.

[0293] Crystalline polyester (C1) 200 parts by mass

[0294] <Mixed solution [5]> Methyl ethyl ketone 120 parts by mass Isopropyl alcohol 30 parts by weight

[0295] Thereafter, the heating temperature was raised to 67° C., and ion-exchanged water was added dropwise at a rate of 8 g / min using a pump while stirring. When the amount of ion-exchanged water being fed reached 580 parts by mass, the addition of ion-exchanged water was stopped.

[0296] Thereafter, the solvent was removed under reduced pressure to prepare a dispersion liquid (c) of crystalline polyester particles. Ion-exchanged water was added to this dispersion liquid (c) to adjust the solid content to 25% by mass, thereby preparing a crystalline polyester particle dispersion liquid (c1). The volume-based median diameter (d50) of the crystalline polyester particles contained in the crystalline polyester particle dispersion liquid (c1) was measured using Microtrac UPA-150 (manufactured by Nikkiso Co., Ltd.) and found to be 198 nm.

[0297] (D.4) Preparation of release agent particle dispersion (W1) The release agent, surfactant, and ion-exchanged water shown below were mixed in the amounts shown below, and the release agent was dissolved in a pressure discharge homogenizer (Gaulin Homogenizer manufactured by Gaulin Co., Ltd.) at an internal liquid temperature of 120°C.

[0298] "FNP0090" (release agent) 270 parts by weight "Neogen RK" (surfactant) 13.5 parts by mass Ion-exchanged water: 21.6 parts by weight

[0299] The release agent "FNP0090" (manufactured by Nippon Seiro) is a paraffin wax and has a melting temperature of 89°C.

[0300] Moreover, the above-mentioned surfactant "Neogen RK" (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) is an anionic surfactant.

[0301] After that, the dispersion was treated at a dispersion pressure of 5 MPa for 120 minutes, then at 40 MPa for 360 minutes, and cooled to obtain a dispersion liquid (w). Further, ion-exchanged water was added to the dispersion liquid (w) so that the solid content was 20%, and this was used as a release agent particle dispersion liquid (W1). The volume average particle size of the particles in the release agent particle dispersion liquid (W1) was 215 nm.

[0302] (D.5) Preparation of black colorant particle dispersion (1) The following resistance adjuster, surfactant and ion-exchanged water were mixed in the amounts shown below, and pre-dispersed for 10 minutes using a homogenizer (ULTRA-TURRAX T50, manufactured by IKA).

[0303] "REGAL (registered trademark) 330" (resistance adjuster) 100 parts by weight "Neogen SC" (surfactant) 15 parts by weight Ion-exchanged water 400 parts by weight

[0304] The above-mentioned "resistance adjuster" is carbon black (manufactured by Cabot Corporation). The above surfactant is an anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).

[0305] Thereafter, a high-pressure impact dispersing machine, Ultimizer (manufactured by Sugino Machine), was used to carry out a dispersion process at a pressure of 245 MPa for 30 minutes to obtain an aqueous dispersion of black colorant particles. Ion-exchanged water was further added to this aqueous dispersion of black colorant particles to adjust the solid content to 15 mass%, and this was used as black colorant particle dispersion (1). The volume-based median diameter (d50) of the colorant particles in the black colorant particle dispersion (1) was measured using Microtrac UPA-150 (manufactured by Nikkiso Co., Ltd.) and was found to be 110 nm.

[0306] (D.6) Preparation of toner base particles (1) (Agglomeration / fusion process and maturation process) The dispersion liquid prepared in the above (D.1) to (D.5), a surfactant, and ion-exchanged water were placed in a 4-liter reaction vessel equipped with a thermometer, a pH meter, and a stirrer in the amounts shown below, and 1.0% nitric acid was added at 25°C to adjust the pH to 3.0 to prepare a raw material dispersion liquid.

[0307] Amorphous polyester particle dispersion (a1) 1008 parts by mass Amorphous vinyl resin particle dispersion (b1) 32 parts by mass Crystalline polyester particle dispersion (c1) 160 parts by mass Release agent particle dispersion (W1) 160 parts by weight Black colorant particle dispersion (1) 187 parts by weight "Dowfax2A1" (surfactant) 40 parts by weight Ion-exchanged water 1500 parts by weight

[0308] The above surfactant is an anionic surfactant.

[0309] Thereafter, 100 parts by mass of a flocculant was added dropwise over 30 minutes while dispersing at 3000 rpm using a homogenizer "ULTRA-TURRAX T50" (manufactured by IKA). As the flocculant, an aqueous solution of aluminum sulfate with a concentration of 2% was used.

[0310] After the dropping of the coagulant was completed, the mixture was stirred for 10 minutes to thoroughly mix the raw material dispersion and the coagulant. Then, a stirrer and a mantle heater were installed in the reaction vessel.

[0311] While adjusting the rotation speed of the stirrer so that the slurry was sufficiently stirred, the temperature inside the reaction vessel was increased at a rate of 0.2°C / min until the temperature reached 40°C.

[0312] After the temperature inside the reaction vessel exceeded 40°C, the temperature was increased at a rate of 0.05°C / min, and the particle size was measured every 10 min using a Coulter Multisizer 3 (aperture diameter 100 μm, manufactured by Beckman Coulter).

[0313] When the volume-based median diameter of the particles in the above raw material dispersion reached 3.9 μm, the temperature was maintained and a mixture of the following amorphous polyester particle dispersion (a1) and a surfactant, which had been mixed in advance, was added to the reaction vessel over a period of 20 minutes.

[0314] <Mixed liquid> Amorphous polyester particle dispersion (a1) 400 parts by mass "Dowfax2A1" (surfactant) 15 parts by weight

[0315] The above surfactant is an anionic surfactant.

[0316] Next, the inside of the reaction vessel was kept at 50°C for 30 minutes, and then 8 parts by mass of 20% EDTA (ethylenediaminetetraacetic acid) solution was added to the reaction vessel. Then, 1 mol / L aqueous sodium hydroxide solution was added to the reaction vessel, and the pH of the raw material dispersion in the reaction vessel was controlled to 9.0. Then, the temperature was raised to 85°C at a rate of 1°C / min while adjusting the pH to 9.0 every 5°C, and the temperature was kept at 85°C.

[0317] (cooling process) Thereafter, using "FPIA-3000," the solution was cooled at a temperature drop rate of 10° C. / min when the shape factor reached 0.970, to prepare a toner base particle dispersion (1).

[0318] (filtration, washing and drying processes) Thereafter, the toner base particle dispersion liquid (1) was filtered, thoroughly washed with ion-exchanged water, and then dried at 40° C. to prepare toner base particles (1). The prepared toner base particles (1) had a volume-based median diameter of 4.0 μm and an average circularity of 0.971.

[0319] (D.7) Addition of external additives The following external additives were added in the amounts shown below to the toner base particles (1) prepared above, and mixed using a Henschel mixer (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.).

[0320] <External additives> Hydrophobic silica (number average primary particle size 12 nm, hydrophobicity degree 68) 1.0% by mass Hydrophobic titanium oxide (number average primary particle size 20 nm, hydrophobicity degree 64) 1.5% by mass

[0321] Thereafter, coarse particles were removed using a sieve with 45 μm openings to prepare "Toner 1."

[0322] E. Preparation of Developer (E.1) Preparation of the developer Carrier 1 prepared in (C.1) to (C.4) above and toner 1 prepared in (D.1) to (D.7) were charged into a V-type mixer in the amounts shown below, and mixed for 5 minutes under normal temperature and humidity conditions to prepare developer 1.

[0323] Carrier 1 100 parts by weight Toner 1 6 parts by weight

[0324] (E.2) Preparation of developers 2 to 14 Developers 2 to 14 were prepared in the same manner as in Developer 1, except that the type of carrier was changed from Carrier 1 as shown in Table V.

[0325] [Table 5]

[0326] F. Evaluation: Image defect due to charge leakage (white spots) (Evaluation method) The photoconductor, developer carrier, and developer were installed in the commercially available color multifunction printer "bizhub C450i" (manufactured by Konica Minolta, Inc.) in the combination shown in Table VI, and the V 0 =-550V, Vdc=-400V, frequency=4kHz, Vpp=1.5kV, POD gloss coat (A3 size, 100g / m 2 Ten sheets were printed onto a paper sheet (Oji Paper Co., Ltd.).

[0327] In addition, V 0 is the surface potential of the photoconductor, Vdc is the DC voltage, and Vpp is the minimum value of the AC voltage waveform (Vp 1 ) and maximum value (Vp 2 ) absolute value of the difference (|Vp 1 -Vp 2 |) (see Figure 5). At this time, the DC voltage Vdc is (Vp 1 -Vp 2 ) / 2.

[0328] Continuous printing of 2,000 sheets of A4 size with a print rate of 5% was performed in a normal temperature and humidity environment (temperature 20°C, humidity 50% RH). After the continuous printing, the photosensitive drum was rotated once to produce an evaluation printout consisting of a halftone image with an image density of 0.4 and a solid image with an image density of 1.1. The number of image defects (white spots) formed on the evaluation printout was counted and evaluated according to the following evaluation criteria.

[0329] Grades A, B, and C, which have no practical problems, were rated as pass, while grades D and E, which have practical problems, were rated as fail.

[0330] (Evaluation Criteria) A: The number of image defects (white spots) is within the range of 0 to 3 (passing: particularly excellent). B The number of image defects (white spots) is within the range of 4 to 8 (pass). C The number of image defects (white spots) is within the range of 9 to 12 (pass). D The number of image defects (white spots) is within the range of 13 to 19 (fail). E The number of image defects (white spots) is 20 or more (fail). G. Evaluation: Image density decrease under low temperature and low humidity conditions (Evaluation method) A photoconductor, developer carrier, and developer were mounted in the combinations shown in Table VI in a commercially available color multifunction printer "bizhub C450i" (manufactured by Konica Minolta, Inc.).

[0331] In a low temperature and low humidity environment (temperature 10°C, humidity 20% RH), 2000 continuous prints were made on A4 size paper with a print rate of 5%. After the continuous printing, a solid image was created and the image density was measured and evaluated according to the following evaluation criteria.

[0332] The image density was measured using a fluorescent spectrodensitometer FD-7 manufactured by Konica Minolta, Inc. The light source was D65, and the black density was measured at a 2° viewing angle.

[0333] Grades A, B, and C, which have no practical problems, were rated as pass, while grades D and E, which have practical problems, were rated as fail.

[0334] (Evaluation Criteria) A Image density is 1.50 or more (pass: particularly excellent). B: Image density is within the range of 1.25 or more and less than 1.50 (pass). C Image density is within the range of 1.00 or more and less than 1.25 (pass). D: Image density is within the range of 0.80 or more and less than 1.00 (fail). E Image density is less than 0.80 (fail).

[0335] [Table 6]

[0336] H. General Comment The silicon contents of the photoreceptors and developer carriers of the examples and comparative examples in the combinations shown in Table VI, and the various values ​​and evaluation results related to the carrier contained in the developer are summarized in Table VII.

[0337] [Table 7]

[0338] The meanings of the symbols in Table VII are as follows: CHMA: Cyclohexyl methacrylate St: styrene MMA: Methyl methacrylate MAA: Methacrylic acid BA: Butyl acrylate CB: Carbon black MgO: Magnesium oxide TiO 2 :Titanium dioxide

[0339] As can be seen from Table VII, unlike the evaluation of the comparative example, the evaluation of the examples did not give the ratings of "D" or "E" in the evaluation of image defects (white spots) due to charge leakage and image density in a low temperature and low humidity environment (LL image). From this, it can be seen that the examples can suppress localized image defects due to charge leakage and reduction in image density in a low temperature and low humidity environment. [Explanation of symbols]

[0340] 10 Developing roller 11 Developing sleeve 12 Magnet Roller 16 Shaft 17 Bearing section 18 Non-drive side flange 19 Drive side flange 100 Image forming device 110Y, 110M, 110C, 110Bk Image forming unit 111Y, 111M, 111C, 111Bk photoconductor 113Y, 113M, 113C, 113Bk Charging means (charging roller) 115Y, 115M, 115C, 115Bk Exposure means 117Y, 117M, 117C, 117Bk developing means 118Y, 118M, 118C, 118Bk developing roller 119Y, 119M, 119C, 119Bk Cleaning means 131 Intermediate transfer body 133Y, 133M, 133C, 133Bk Transfer means (primary transfer roller) 150 Paper feed conveying means 170 Fixing means 217 Secondary transfer roller (secondary transfer means) SC Original Image Scanner P Transfer material

Claims

1. An image forming system using a two-component developer and an image forming apparatus having at least one of a photoconductor using an aluminum alloy support and a developer carrier made of an aluminum alloy, The static resistance value of the carrier contained in the two-component developer is 1.0×10 12 ~5.0 x 10 14 In the range of Ω cm, and The silicon content in the aluminum alloy forming at least the support of the photoreceptor or the developer carrier is in the range of more than 0.6% by mass and not more than 12.6% by mass.

1. An image forming system comprising:

2. the carrier is made of carrier particles in which at least the surface of a core particle is coated with a coating resin, The coating resin has a structure derived from (meth)acrylate.

2. The image forming system according to claim 1,

3. The coating resin contains at least one of carbon black, magnesium oxide, and titanium dioxide.

3. The image forming system according to claim 2.

4. The exposed area ratio of the core particle on the surface of the carrier particle is in the range of 1.0% or more and less than 10.0% of the surface area of ​​the core particle.

3. The image forming system according to claim 2.

5. The silicon content is in the range of more than 0.8% by mass and not more than 12.6% by mass with respect to the total amount of the aluminum alloy forming at least the support body of the photoreceptor or the developer carrier.

2. The image forming system according to claim 1,

6. The coating resin has a structure derived from an alicyclic (meth)acrylate.

3. The image forming system according to claim 2.

7. The static resistance value of the carrier is 1.0×10 12.5 ~1.5 x 10 14 Within the range of Ω cm 2. The image forming system according to claim 1,

8. The absolute value of the development potential difference is within the range of 300 to 800 V.

2. The image forming system according to claim 1,

9. An image forming method using a two-component developer and an image forming apparatus having at least one of a photoreceptor using an aluminum alloy support or a developer carrier made of an aluminum alloy, comprising: The static resistance value of the carrier contained in the two-component developer is 1.0×10 12 ~5.0 x 10 14 In the range of Ω cm, and The silicon content in the aluminum alloy forming at least the support of the photoreceptor or the developer carrier is in the range of more than 0.6% by mass and not more than 12.6% by mass.

1. An image forming method comprising:

Citation Information

Patent Citations

  • Developing roller and developing apparatus using the same

    JP2008102502A

  • Electrophotographic photoreceptor, process cartridge, and electrophotographic device

    JP2022132142A